Soeharto, 1998 - Husaini, Adian, 1965- (Jakarta : Gema Insani Press, 1996)
Indonesian politics under Soeharto, b. 1921, president of the Republic of Indonesia, after the presidential election, 1998.
Includes bibliographical references (p. 116-117) and index.
Keywords: Soeharto, -- 1921-2008.; Presidents -- Indonesia; Indonesia -- Politics and government -- 1966-